2018
DOI: 10.1155/2018/9303674
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Functional MRI Changes after One Year of Auditory Rehabilitation with Hearing Aids

Abstract: Hearing aids (HAs) are an effective strategy for auditory rehabilitation in patients with peripheral hearing deficits. Yet, the neurophysiological mechanisms behind HA use are still unclear. Thus far, most studies have focused on changes in the auditory system, although it is expected that hearing deficits affect a number of cognitive systems, notably speech. In the present study, we used audiometric evaluations in 14 patients with bilateral hearing loss before and after one year of continuous HA use and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Functional imaging studies show that the degree of neural activity in the occipital cortex in response to a visual stimulus is associated with deafness duration (Shiell, Champoux, & Zatorre, 2015) and post‐CI outcome (Green et al, 2005; Sandmann et al, 2012; Strelnikov et al, 2013; Stropahl et al, 2017). However, we observed no structural changes in the visual cortex in the PD group in relation either to deafness progression or post‐CI outcome, which is in accordance with other structural MRI studies (Peelle et al, 2011; Pereira‐Jorge et al, 2018). This lack of a relationship between structure changes in the visual cortex and post‐CI outcome needs further clarification but indicates that the neural activity in the original visual processing site may not exceed the normal range, thus inducing no structural alteration of the visual cortex in the context of cortical reorganization.…”
Section: Discussionsupporting
confidence: 92%
“…Functional imaging studies show that the degree of neural activity in the occipital cortex in response to a visual stimulus is associated with deafness duration (Shiell, Champoux, & Zatorre, 2015) and post‐CI outcome (Green et al, 2005; Sandmann et al, 2012; Strelnikov et al, 2013; Stropahl et al, 2017). However, we observed no structural changes in the visual cortex in the PD group in relation either to deafness progression or post‐CI outcome, which is in accordance with other structural MRI studies (Peelle et al, 2011; Pereira‐Jorge et al, 2018). This lack of a relationship between structure changes in the visual cortex and post‐CI outcome needs further clarification but indicates that the neural activity in the original visual processing site may not exceed the normal range, thus inducing no structural alteration of the visual cortex in the context of cortical reorganization.…”
Section: Discussionsupporting
confidence: 92%
“…The temporal gyrus is closely related to auditory function, especially the posterior MTG, which is part of the auditory primary cortex. Studies have shown that tinnitus can cause significant cortical changes in the MTG ( Boyen et al, 2013 ; Pereira-Jorge et al, 2018 ). For example, Boyen et al (2013) found that the change in gray matter in the auditory primary cortex (including the MTG) was correlated with tinnitus rather than with HL, and they speculated that the continuous sensation of an internal sound, such as the tinnitus percept, may cause the changes in the MTG.…”
Section: Discussionmentioning
confidence: 99%
“…Postlingual, or late onset, hearing loss is often a comorbidity with tinnitus ( Boyen et al, 2013 , Luan et al, 2019 , Husain et al, 2011 ). General presbycusis ( Peelle et al, 2011 , Lin et al, 2014 , Rigters et al, 2017 , Rigters et al, 2018 ) - acquired hearing loss due to aging - is often comorbid with dementia ( Cunningham and Tucci, 2017 , Reed et al, 2019 , Lin, 2013 ) and confounded by hearing aid use ( Pereira-Jorge et al, 2018 ). Half the people in their 7 th decade or older have hearing loss, which affects communication ( Olkin et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%